Nonlinear DNA methylation trajectories in aging male mice - Maja Olecka; Alena van Bömmel; Lena Best; Madlen Haase; Silke Foerste; Konstantin Riege; Thomas Dost; Stefano Flor; Otto W. Witte; Sören Franzenburg; Marco Groth; Björn von Eyss; et al. (Nature Communications, 2024)
Abstract Although DNA methylation data yields highly accurate age predictors, little is known about the dynamics of this quintessential epigenomic biomarker during lifespan. To narrow the gap, we investigate the methylation trajectories of male mouse colon at five different time points of aging. Our study indicates the existence of sudden hypermethylation events at specific stages of life. Precisely, we identify two epigenomic switches during early-to-midlife (3-9 months) and mid-to-late-life (15-24 months) transitions, separating the rodents’ life into three stages. These nonlinear methylation dynamics predominantly affect genes associated with the nervous system and enrich in bivalently marked chromatin regions. Based on groups of nonlinearly modified loci, we construct a clock-like classifier STageR (STage of aging estimatoR) that accurately predicts murine epigenetic stage. We demonstrate the universality of our clock in an independent mouse cohort and with publicly available datasets.